Sustainability of educational technologies: An approach to ratio and feedback - Mahmud, Malissa Maria; Mat, Nur Huslinda Che; Manap, Mohammad Radzi; Zakaria, Siti Fauziana; Tazijan, Farina; Wong, Shiau Foong (Asian Journal of Contemporary Education, 2023)
Blended learning is a driving force behind new pedagogical approaches. While many studies have shown the positive effects of blended learning on the students’ learning outcomes, the extent and breadth of its sustainability remains an interesting question, given the rapid evolution and diversification of technology post COVID-19 pandemic. In this study, we examined the ratio of technological interventions in blended learning studies, and their corresponding students’ feedback by categorizing 37 compliant articles. With a defined set of inclusion and exclusion criteria, and a clear search strategy, we employed systematic reviews to comprehensively and systematically identify, evaluate, and synthesize relevant evidence to probe on a specific research question. The results advocate the notion of ratio, regardless of its specific percentages, predominantly proffering positive feedback, indicating that the integration of technology is essential for supporting sustainable strategies in teaching and learning approaches. Overall, these findings provide a comprehensive body of high-quality evidence that blended learning has the potential to meritoriously support sustainable education model. It has significant practical significance in addition to its implications for empirical research. Additionally, it produces structured guidelines as a result of its thorough analysis, which may help to accelerate the adoption of blended learning.